2013
DOI: 10.1177/1753425913498912
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Langerhans cell and dry eye examinations in ankylosing spondylitis

Abstract: APCs of the ocular surface, including corneal Langerhans cells (LCs), offer the opportunity to gain insight into the activity of innate immunity. We examined corneal LCs and dry eye parameters in ankylosing spondylitis (AS). Twenty-four AS patients with varying degrees of disease activity and 24 healthy participants were enrolled. Central and peripheral LC numbers, and Langerhans cell morphology (LCM) were assessed with in vivo laser confocal microscopy. In addition, ocular surface disease index, lid parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…15,16,27,33,34 Evaluation of DC in the clinical setting has recently been facilitated by the fact that they can be easily detected and quantified by laser IVCM, 16,26,35,36 with high interobserver agreement in their quantification (R ¼ 0.997; P < 0.001). 37 Using IVCM, although our control group had a DC density within the range reported before, the DED group showed a significantly higher DC density in the central cornea, as has been reported before, [18][19][20][21] with an average increase of 700% compared with the age-matched controls. Furthermore, using a detailed morphologic description of DCs, we demonstrated that in DED these immune cells had a larger cell size with increased number and length of dendrites.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…15,16,27,33,34 Evaluation of DC in the clinical setting has recently been facilitated by the fact that they can be easily detected and quantified by laser IVCM, 16,26,35,36 with high interobserver agreement in their quantification (R ¼ 0.997; P < 0.001). 37 Using IVCM, although our control group had a DC density within the range reported before, the DED group showed a significantly higher DC density in the central cornea, as has been reported before, [18][19][20][21] with an average increase of 700% compared with the age-matched controls. Furthermore, using a detailed morphologic description of DCs, we demonstrated that in DED these immune cells had a larger cell size with increased number and length of dendrites.…”
Section: Discussionsupporting
confidence: 81%
“…6,7 Given their established role in immune regulation of the ocular surface, [5][6][7] there has been a recent interest in evaluation of their alterations in various ocular surface diseases. Recent studies have shown that the DC density significantly increases in various conditions such as DED, [17][18][19][20][21]29 corneal graft rejection, 5,30 contact lens wear, 22,31 and infectious keratitis. 32 In addition to changes in DC density, the morphology of these cells changes upon stimulation, resulting in maturation of these cells with an increase in cell size and formation and lengthening of dendritic processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies have shown a difference in cell infiltration rates in Sjögren's compared to non‐Sjögren's dry eyes, while activity of innate immunity in ankylosing spondylitis and rheumatoid arthritis has also been associated with Langerhans cells density and morphology.…”
Section: Corneal Confocal Microscope In Other Peripheral Neuropathiesmentioning
confidence: 99%
“…However, keratoconjunctivitis sicca (KCS), generally known as dry eye disease (DED), could also occur [2][3][4] . There are few and inconsistent reports regarding the simultaneous occurrence of AS and DED, even though the eye dry eye tests performed in these studies were incomplete [5][6][7] .…”
mentioning
confidence: 99%